Analisis Spasial Pengaruh House Index dengan Kasus DBD di Kecamatan Bangilan Kabupaten Tuban - Barokatul Aulia Izza; Ngadino Ngadino; Demes Nurmayanti; Marlik Marlik; Yudied Agung Mirasa (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2022)
Dengue Hemorrhagic Fever (DHF) in Tuban Regency was an important health problem. Bangilan sub-district is a sub-district in Tuban Regency which has high dengue cases. The Bangilan Health Center has not used mapping or spatial analysis in its surveillance activities for dengue cases. Disease mapping is useful in assisting surveillance activities and making it easier for us to find out the spread of the house index in each village area. The purpose of this study is to analyze the spatial house index with dengue cases in Bangilan District, Tuban Regency. This type of research is descriptive analytic. The population in this study is a house around DHF patients with a radius of 100 m from the patient's house in Bangilan District, with a total sample of 774 houses. The research variables were cases of DHF and house index. DHF cases in 2020-2022 were obtained from secondary data from the Bangilan Health Center, while the house index was obtained from the larvae survey results. The data were analyzed to determine the effect of the house index and dengue cases using the GeoDa application. The results showed that the average house index in Bangilan District was 20.8% which according to WHO was high. The pattern of spread of DHF cases is random with an Average Nearest Neighbor value = 1 and the results of Moran's Index (I) = 0.061, meaning that there is a strong spatial autocorrelation effect on the house index with DHF cases.